PTU-200 Why do crohn's and idiopathic anal fistulae persist?. (22nd June 2015) - Yassin, NA; Al-Hassi, H; Ansari, T; Knight, S; Sibbons, P; Hart, A; Phillips, R
Abstract : Introduction: An interaction between genetic, microbiological and immunological factors drives Crohn's disease. Bacterial infection probably initiates idiopathic anal fistulae but does not maintain them. Dendritic cells (DC) express Toll-Like receptors (TLR), which are pattern recognition receptors that are activated by bacterial ligands. We compared the expression of TLRs and microbiota profiles of CD and idiopathic fistulae. Method: Biopsies were taken from 35 Crohn's and 25 idiopathic fistulae at surgery. DC were identified as HLA-DR-positive and lineage-negative, and characterised by flow cytometry using fresh samples. The expression of TLR2 and 4 was determined. Immunohistochemical techniques determined the expression of TLR2, TLR4 and TLR9 on paraffin-imbedded biopsies. DNA was extracted from frozen samples and bacterial 16S rRNA genes were sequenced using a MiSeq sequencer. Results: TLR2 and 4 were expressed on DC from both Crohn's and idiopathic perianal fistulae using flow cytomtery. There was no significant difference in TLR2 (p = 0.27) or TLR4 (p = 0.45) expression on CD and idiopathic fistulae. Immunohistochemistry showed equal expression of TLR2 (p = 0.42) and TLR4 (p = 0.11) on lymphocytes. TLR9 expression was significantly higher in CD fistulae (p = 0.01). Microbiota were classified as common and abundant, infrequent, and rare. The total number of operational taxonomic units (OTUs) observed and the number of species identified in Crohn's fistulae was significantly higher than idiopathic (p = 0.02). The most abundant species in the Crohn's group were Bradyrhizobium pachyrhizi followed by Pseudomonas azotoformans and Prevotella oris. Conclusion: Bacterial products and the local immune response to them are present in perianal fistula tracts. Fistula persistence may be driven by bacterial products rather than live bacteria. This could provide therapeutic treatment targets for Crohn's anal fistulae. Disclosure of interest: None Declared.